Anti-Corruption model: Optimization of accountability and transparency, law enforcement, and anti-corruption agencies in Indonesia - Rohman, Fatkhur; Fathia, Syaharani Noer (Lighthouse Publishing, 2024)
Corruption practices are deviations from norms in the form of fraud (fraud) involving illegal actions for personal gain. In Indonesia, anti-corruption practices are still repressive while preventive measures are minimally implemented. This is one of the factors causing Indonesia to be ranked 96th out of 180 countries in 2021 with a Corruption Perceptions Index score of 38/100, meaning Indonesia is still massively plagued by corruption practices and requires optimization in corruption eradication. The purpose of this research is to contribute to anti-corruption studies by optimizing the role of transparency and accountability, law enforcement, and anti-corruption agencies in Indonesia so that the government can effectively eradicate corruption. This research is a literature review. this research aims to produce an outcome in the form of a concept of corruption mitigation in government agencies by improving the accountability and transparency of institutions. This research prove that integrated approach is needed to eradicate the corruption cases within the Transparency and accountabiltity, law enforcement and anti-corruptions agencies in Indonesia.